2021
DOI: 10.25077/jpt.5.1.24-33.2021
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Detection of Phytohormone (Gibberellic Acid and Indole Acetic Acid) Produced by Fusarium spp. that Causes Twisted Disease in Shallot

Abstract: The twisted disease is one of the essential diseases in shallots caused by Fusarium spp. This study aimed to study pathogenicity and identify Fusarium species isolated from shallot plants with twisted symptoms in Nganjuk and Bantul areas. The Fusarium isolates were identified and then tested for pathogenicity levels and the effect of the hormones GA3 and IAA on shallot symptoms. Molecular identification using NF2 and NF4 successfully identified one isolate of Fusarium oxysporum, three isolates of F. acutatum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…The effect of different treatments in this study on biochemical changes was assayed and tabulated in Table (7 (Junaidi andBolhassan, 2017 andLestiyani et al, 2021) and Gibberellic acid (Ben Rhouma et al, 2020 andLestiyani et al, 2021).…”
Section: -Biochemical Changesmentioning
confidence: 99%
“…The effect of different treatments in this study on biochemical changes was assayed and tabulated in Table (7 (Junaidi andBolhassan, 2017 andLestiyani et al, 2021) and Gibberellic acid (Ben Rhouma et al, 2020 andLestiyani et al, 2021).…”
Section: -Biochemical Changesmentioning
confidence: 99%
“…The pathogen used for inoculation was Fusarium acutatum as it has the highest virulence among other twisted-causing pathogens (Lestiyani et al, 2021). F. acutatum isolates were grown on Potato Dextrose Agar (PDA) medium for seven days, then the spores were harvested and suspended to obtain a spore density of 10 6 CFU/ml.…”
Section: Pathogen Inoculationmentioning
confidence: 99%
“…These pathogens species have different roles in the onset of the symptoms. The infection of F. solani and F. acutatum caused wilting symptoms on plants, F. solani, F. oxysporum and F. acutatum caused tuber rotting, while the typical symptoms of twisted (leaf twisting and wilting) were caused by F. solani and F. acutatum (Lestiyani et al, 2021). The biological control agent widely used by growers and proven to suppress disease in shallots is Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Another pathogen Gibberella moniliformis was reported to produce overlapping symptoms of twisting and abnormal neck elongation in onions due to the excessive accumulation of gibberellins 17 . Lestiyani et al 18 reported onion twister is caused by Fusarium oxysporum, F. solani, and F. acutatum . Though, each species playing different role in symptom development i.e., F. solani and F. acutatum causes wilting; F. solani, F. acutatum or F. oxysporum causes bulb rotting, the twisting symptoms were caused by F. solani or F. acutatum .…”
Section: Introductionmentioning
confidence: 99%